PL.89 Functional Effects of Oestradiol on Cytokine Responses of Human Ectocervical Epithelial Cells to Toll-Like Receptor 2 and 4 Ligands. (26th April 2013) - Lashkari, BS; Anumba, DOC
Abstract : We have demonstrated that the pattern recognition toll-like receptors (TLR) 2&4 are upregulated during pregnancy in human cervical epithelium. We sought to determine whether oestradiol (E2 ) alters the immunological responses of cultured human ecto-cervical epithelial cells (HECECs) to the ligands of TLR2 (peptidoglycan, PGN) and TLR4 (lipopolysaccharides, LPS). Methods and Material: Fresh ectocervical tissues were collected from hysterectomy specimens, epithelia isolated and cultured after collagenase and trypsin digestion, cell purity being validated by immunofluorescence. The expression of TLRs 2&4, and E2 receptor genes (ERs α&β) were demonstrated by flow cytometry and RT-PCR respectively. HECECs were co-incubated with varying E2 concentrations (0.1, 1, 10, 100 nM) and PGN (50 μg/ml) or LPS (100 ng/ml) for 10 min, 2 hrs and 18 hrs. Cytokines were assayed in supernatant fluid by Cyto-Bead Array. Result: In response to PGN, HECECs co-incubated with E2 released lower levels of IFN-γ, IL-6 and IL-8, whilst after 18 hrs, RANTES expression increased to low E2 but decreased to high E2. In response to LPS, HECECs co-incubated with E2 demonstrated increased expression levels of IL-10, IL-12p70, RANTES and TNFα at 10 min and 2 hrs. IL-6 and IL-8 levels increased at 2 hrs but were suppressed or unchanged after 18 hrs. Markedly increased levels of RANTES were detected after 18 hrs, an effect obtunded by culturing HECECs in E2. Discussion: The complex immunomodulatory effects of E2 on cultured HECECs appear to vary with bacterial ligands and duration of exposure, suggesting direct non-genomic vs. genomic mechanisms. The resulting cytokine profiles may contribute to cervical remodelling during pregnancy.